Property theory legal and political perspectives - Penner, J. E. ca. 20./21. Jh; Otsuka, Michael 1964- (Cambridge University Press, 2018)
Property, or property rights, remains one of the most central elements in moral, legal, and political thought. It figures centrally in the work of figures as various as Grotius, Locke, Hume, Smith, Hegel and Kant. This collection of essays brings fresh perspective on property theory, from both legal and political theoretical perspectives, and is essential reading for anyone interested in the nature of property. Edited by two of the world's leading theorists of property, James Penner and Michael Otsuka, this volume brings together essays which consider, amongst other topics, property and public law, the importance of legal forms in property theory, whether use or exclusion are most essential to our understanding of property, distributive justice, Lockean and Grotian theories, the common ownership of the Earth, and Confucian ideas of property
Title from publisher's bibliographic system (viewed on 30 Aug 2018)
Machine generated contents note: 1. The public nature of private property Lisa M. Austin; 2. Legal forms in property law theory Larissa Katz; 3. What is the right to exclude and why does it matter? James Y. Stern; 4. Using things, defining property Christopher M. Newman; 5. Is original acquisition problematic? Nicholas Sage; 6. Appropriating Lockean appropriation on behalf of equality Michael Otsuka; 7. Rights, distributed and undistributed: on the distributive justice implications of Lockean property rights, especially in land James Penner; 8. Lockean property theory in Confucian thought: property in the thought of Wang Fuzhi (1619-92) and Huang Zongxi (1610-95) Norman P. Ho; 9. Two ways of theorising 'collective ownership of the earth' Johan Olsthoorn
Keywords: Locke, John -- 1632-1704; Ideengeschichte; Right of property; Eigentum; Politische Theorie; Philosophie; Rechtstheorie